Key Aging-Associated Alterations in Primary Microglia Response to Beta-Amyloid Stimulation - Caldeira, Cláudia; Cunha, Carolina; Vaz, Ana R.; Falcão, Ana S.; Barateiro, Andreia; Seixas, Elsa; Fernandes, Adelaide; Brites, Dora (Frontiers in Aging Neuroscience, 2017)
Alzheimer’s disease (AD) is characterized by a progressive cognitive decline and believed to be driven by the self-aggregation of amyloid-β peptide (Aβ) into oligomers and fibrils that accumulate as senile plaques. It is widely accepted that microglia-mediated inflammation is a significant contributor to disease pathogenesis; however, different microglia phenotypes were identified along AD progression and excessive Aβ production was shown to dysregulate cell function. So, the contribution of microglia to AD pathogenesis remains to be elucidated. In this study, we wondered if isolated microglia cultured for 16 days in vitro (DIV) would react differentially from the 2 DIV cells upon treatment with 1000 nM Aβ1-42 for 24 h. No changes in cell viability were observed and morphometric alterations associated to microglia activation, such as volume increase and process shortening, were obvious in 2 DIV microglia, but less evident in 16 DIV cells. These cells showed lower phagocytic, migration and autophagic properties after Aβ treatment than the 2 DIV cultured microglia. Reduced phagocytosis may derive from increased CD33 expression and reduced TREM2 and MFG-E8 levels mainly observed in 16 DIV cells. Activation of inflammatory mediators (HMGB1 and pro-inflammatory cytokines) and of TLR2, TLR4 and CX3CR1 cell surface receptors were prominent in 2 DIV microglia, while elevation of MMP9 was marked in 16 DIV cells. Senescence-associated β-galactosidase and upregulated miR-146a expression were observed in 16 DIV cells and increased by Aβ in 2 DIV microglia. Additionally, Aβ downregulated miR-155 and miR-124, and reduced the CD11b+ subpopulation in 2 DIV microglia, while increased the number of CD86+ cells in 16 DIV microglia. Simultaneous M1 and M2 markers were found after Aβ treatment, but at lower expression in the in vitro aged microglia. Data show key-aging associated responses by microglia when incubated with Aβ, with a loss of reactivity from the 2 DIV to the 16 DIV cells, which course with a reduced phagocytosis, migration and lower expression of inflammatory miRNAs. These findings help to improve our understanding on the heterogeneous responses that microglia can have along the progression of AD disease and imply that therapeutic approaches may differ from early to late stages.